PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN BIOLOGI MATERI SUBSTANSI GENETIKA - DINDARDIYA, RAHAYU; U.S, SUPARDI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2024)
This study aims to determine whether learning through Audio Visual media can improve the learning outcomes of biology students in class XII IPA 3 SMA Negeri 1 Cibitung on the substance of genetics. The method used is class action research (PTK) which consists of two cycles. The research subjects were XII IPA 3 class of SMA Negeri 1 Cibitung as many as 36 students. Data analysis used a comparative descriptive quantitative method, namely by comparing student test scores, observation results of student and teacher activities from initial conditions with the results achieved from each cycle and analyzed in cycle I and cycle II with the application of Audio Visual media. At the end of cycle II, it is known that there has been an increase, namely from cycle I students who completed 77.77% with an average student score of 77.12. In cycle II students who completed as many as 94.44% with an average class score of 84.54. In addition to the intu, student learning activities also increased from Cycle I as much as 83.33% with an average student score of 87. in cycle II to 91.66% with an average student score of 94. Thus most students of class XII IPA 3 SMA Negeri 1 Cibitung experienced an increase in learning outcomes through the use of Audio Visual media on genetic substance material. ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah pembelajaran melalui media Audio Visual dapat meningkatkan hasil belajar biologi siswa kelas XII IPA 3 SMA Negeri 1 Cibitung pada materi substansi genetika. Metode yang digunakan adalah penelitian tindakan kelas (PTK) yang terdiri atas dua siklus. Subjek penelitian adalah kelas XII IPA 3 SMA Negeri 1 Cibitung sebanyak 36 siswa. Analisis data menggunakan metode kuantitatif desktiftif komparatif, yaitu dengan membandingkan nilai tes siswa, hasil observasi terhadap kegiatan siswa dan guru dari kondisi awal dengan hasil-hasil yang dicapai dari setiap siklus dan analis pada siklus I dan siklus II dengan penerapan media Audio Visual. Pada akhir siklus II diketahui telah terjadi peningkatan yaitu dari siklus I siswa yang tuntas sebanyak 77,77 % dengan nilai rata-rata siswa 77,12. Pada siklus II siswa yang tuntas sebanyak 94,44% dengan nilai rata-rata kelas 84,54. Selain intu aktivitas belajar siswa juga mengalami peningkatan dari Siklus I sebanyak 83,33 % dengan nilai rata -rata siswa 87. pada siklus II menjadi 91,66 % dengan nilai rata-rata siswa 94. Dengan demikian sebagian besar siswa kelas XII IPA 3 SMA Negeri 1 Cibitung mengalami peningkatan hasil belajar melalui penggunaan media Audio Visual pada materi substansi genetika.